Brassica rapa selenium transporter NPF2.20 (BrNPF2.20) accounts for Se-enrichment in Chinese cabbage - Xiaoting Hu; Yucheng Chen; Weihong Xu (Ecotoxicology and Environmental Safety)
Selenium (Se) is an essential nutrient for the human body and breeding highly Se-enriched Chinese cabbage varieties is an important means of addressing Se deficiency in individuals in certain regions. The genus Brassica has a strong ability to enrich Se; however, the primary molecular mechanism of Se enrichment remains unclear. We screened for high- and low-Se-enriched Chinese cabbage varieties from 39 different genotypes and identified a key candidate gene for Se enrichment, namely, BrNPF2.20 (BraA07g035670.3.1 C), located on the cell membrane. The expression level of BrNPF2.20 in the high-Se-enriched Chinese cabbage variety P2 was significantly higher than that in the low-Se-enriched variety P6. Heterologous expression of BrNPF2.20 increased the sensitivity of yeast to Se. The overexpression of BrNPF2.20 significantly increased the Se content in Arabidopsis plants, whereas silencing BrNPF2.20 in Chinese cabbage leaves reduced the Se content. Cell selenium mainly in the cell wall may be the physiological and biochemical mechanism of the high-Se-enriched vareity in response to selenium stress. BrNPF2.20 promoted the transport and accumulation of Se from root to shoot in Chinese cabbage maybe by increasing GSH-Px activity or regulating sulfate transporter family genes related to Se absorption and transport. This study not only deepens our understanding of Se transport from Chinese cabbage root to the ground part, but also provides a new idea for breeding Se-rich Chinese cabbage varieties by promoting SeMet transport.